2019
DOI: 10.18203/2320-1770.ijrcog20191207
|View full text |Cite
|
Sign up to set email alerts
|

Partogram and its relevance in modern obstetrics

Abstract: Background: Normal labor and childbirth is fraught with complexities. In the modern times the child birth has proven to be more challenging than ever. Partogram has proven to be a simple and useful tool in monitoring normal labor. The objective of this endeavor was to site our experiences in using partogram for ‘plotting’ labors, to assess its utility, limitations and cite controversies.Methods: Authors analyzed progress of labor plotted on partograms in parturient women to see whether their labor patterns con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Since the publication of Philpott's study in 1972, the use of partograph has shown to reduce maternal and fetal mortality and morbidity. Philpott's work was inspired by Friedman's cervicograph [17].…”
mentioning
confidence: 99%
“…Since the publication of Philpott's study in 1972, the use of partograph has shown to reduce maternal and fetal mortality and morbidity. Philpott's work was inspired by Friedman's cervicograph [17].…”
mentioning
confidence: 99%